A 6DOF super element for nonlinear analysis of composite frames with partial interaction and semi-rigid connections - Bao Nghi, Le Luong; Cong Thanh, Bui (Vietnam Journal of Mechanics, 2011)
This paper presents a displacement-based finite element formulation for nonlinear analysis of steel - concrete composite planar frames subjected to combined action of gravity and lateral loads. A 6DOF super element is proposed for modeling composite beam, allowing for partial interaction between the steel beam and the concrete slab, semi-rigid nature of beam to column composite connection and material nonlinearity. The load control method and the displacement control method are utilized for tracing the structural equilibrium paths, and the direct method is utilized for solving the nonlinear problem. Numerical examples, concerning a two-span continuous composite beam, a portal composite frame and a six-storey composite frame, are performed. The results are compared with experience data or theoretical results from other studies and are discussed for influences of the factors mentioned above on behaviour of composite beams and composite frames.